IMPLEMENTASI BELA NEGARA BAGI GENERASI Z DI ERA DIGITAL DALAM BINGKAI NILAI-NILAI PANCASILA - Karimatunnisa Karimatunnisa (CV. KAMPUS AKADEMIK PUBLISING, 2026)
State defense is a constitutional obligation of every Indonesian citizen as mandated in the 1945 Constitution of the Republic of Indonesia. In the rapidly evolving digital era, Generation Z as the cohort that grew up alongside information and communication technology holds a strategic role in implementing the values of state defense. This study aims to analyze the relevant forms of state defense implementation for Generation Z as well as the challenges and opportunities faced in manifesting the spirit of state defense in the digital age. The method used is qualitative research with a library research approach. Data were collected from various literary sources including books, scientific journals, articles, legislation, and relevant digital sources. The results show that Generation Z can implement state defense through non-military means, including digital literacy, counter-narratives against radicalism and hoaxes, active participation in national life online, and the use of digital platforms to strengthen national identity. The main challenges include threats of digital disintegration, disinformation spread, and national identity crisis. This study concludes that state defense for Generation Z does not have to take a military form, but can be expressed through concrete actions in the digital realm that contribute to national resilience.